1994
DOI: 10.20506/rst.13.3.804
|View full text |Cite
|
Sign up to set email alerts
|

Use of life and inactivated Salmonella enteriditid=s phage type 4 vaccines to immunise laying hens against experimental infection

Abstract: Four groups of Dekalb Delta commercial layer hens (8 hens per group) were reared individually in cages in an isolation unit. At the age of 8 weeks, groups 1 and 2 were vaccinated with 9R Salmonella gallinarum live (9R live) vaccine. At the age of 18 weeks, group 1 was re-vaccinated with 9R live S. enteritidis vaccine, while groups 2 and 3 were vaccinated with S. enteritidis bacterin. At the age of 22 weeks, groups 2 and 3 were re-vaccinated with S. enteritidis bacterin. Group 4 was not vaccinated and was kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In one study, an attenuated ST vaccine strain was shown to offer protection against SE virulent challenge in chickens ( 31 ). One report also demonstrated the protection efficacy of SG vaccines against virulent SE infections in laying hens ( 32 , 33 ). In our previous studies, we constructed a live attenuated ST strain ( 34 ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In one study, an attenuated ST vaccine strain was shown to offer protection against SE virulent challenge in chickens ( 31 ). One report also demonstrated the protection efficacy of SG vaccines against virulent SE infections in laying hens ( 32 , 33 ). In our previous studies, we constructed a live attenuated ST strain ( 34 ).…”
Section: Introductionmentioning
confidence: 95%
“…In our previous studies, we constructed a live attenuated ST strain ( 34 ). As several other studies previously explored the cross-protection conferred by Salmonella vaccines against related serovars ( 31 , 32 , 33 , 35 ), immunization with this ST strain may confer protection against salmonellosis.…”
Section: Introductionmentioning
confidence: 96%
“…Different types of salmonella vaccines have been used in chickens to immunize and protect against excretion of salmonella; however, complete protection against the elimination of highly infectious serotypes immediately after challenge has not yet been achieved (Nassar et al 1994, Freitas Neto et al 2008, Atterbury et al 2009, Revolledo & Ferreira 2010.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of live vaccines is variable and not always satisfactory because residual virulence may remain that requires host clearance (Matsui et al., ; Takaya et al., ; Singh, ). The efficacy of live vaccines in poultry has been examined in experimental and field studies, but to our knowledge, only a few studies have shown improvements in the protective effect of immunization against egg contamination (Nassar et al., ; Hassan and Curtiss, ; Gantois et al., ).…”
Section: Introductionmentioning
confidence: 99%